LITHIC TECHNOLOGY OF THE SOSRUKO ROCKSHELTER EARLY HOLOCENE INDUSTRIES - Es'kova, Dar'a Kirillovna (History, Archeology and Ethnography of the Caucasus, 2023)
The paper discusses the emergence and spread of pressure blademaking in the Elbrus region of the North Caucasus. The results of the lithic technology analysis of the key stratified site of the Mesolithic Layers M-1 and M-2 of the Sosruko Rockshelter are presented. The materials from the excavations of 1955-1957, conducted by S.N. Zamyatnin and P.G. Akritas, were considered. There are few but unquestionable signs of the pressure blademaking use in Layer M-2 dated to the second half of the 10th mil. BC. The full operational chain of bladelet production with the use of pressure technique was revealed in Layer M-1 dated to the second quarter of the 9th mil. BC – the beginning of the 8th mil. BC. The pressure Mode 1 (manual pressure) was used to produce the microbladelets and narrow bladelets with the flint heat treatment. Moreover, the pressure cores had a wide flaking surface with the linear distal end and a slightly inclined facetted platform. The blades in the industries of Layers M1 and M-2 were produced with the direct percussion. The studied Early Holocene industries of the Sosruko Rockshelter differ significantly from the partly synchronous industries of the North-Western Caucasus. The studied tradition had presumably local distribution. It finds analogy in the lithic industries of Layer 7 of Horizons 1-4 of the Badynoko Rockshelter (the Elbrus region). The correlation between the emergence of the simplest mode of the pressure blademaking in the Elbrus region in the Early Holocene and the distribution of the innovation in the neighboring regions is disputable. The possibility of the independent invention of the pressure blademaking in the Elbrus region cannot be completely rejected. On the contrary, the Elbrus Early Holocene industries could have been the source of the Mode 1 pressure technique distribution in the South Caucasus.
Keywords: Mesolithic; North Caucasus; Elbrus region; lithic technology; pressure technique; chronology